The fear of happiness : exploring its antecedents and consequences on well-being - Yang, YingJia (2018)
Although people generally prefer being happy than unhappy, research suggests that certain individuals might possess a fear of happiness, and that such fear might be more prominent in certain cultures (Joshanloo et al., 2014). The current study aimed to examine the explanatory mechanisms involved in the antecedent and consequences of fear of happiness. Based on previous cross-cultural research (Markus & Kitayama, 1991), I examined independent and interdependent self-construal, and the associated dialectical thinking style as the antecedent mechanism of fear of happiness. Based on previous research on emotion regulation (Bryant & Veroff, 2007; Nelis et al., 2010), I examined dampening of positive emotions as the explanatory mechanism for the consequences of fear of happiness on well-being. Undergraduates in Singapore (N = 117) completed self-reports on independent and interdependent self-construal, dialectical thinking, fear of happiness, dampening of positive emotions, and four well-being measures – affect, life satisfaction, psychological well-being, and integrative well-being. Mediation analyses showed that interdependent self-construal did not predict fear of happiness. However, lower independent self-construal predicted higher dialectical thinking, which in turn predicted higher fear of happiness. Also, higher fear of happiness predicted increased dampening of positive emotions, which in turn predicted lower positive affect. Although similar results were found on the other three measures of well-being, the effects were no longer significant after controlling for affect. Results demonstrated the cognitive mechanisms involved in the antecedent and consequences of fear of happiness. Theoretical and practical implications for cultural research on fear of happiness and well-being will be discussed.